2010
DOI: 10.1590/s0004-27302010000800004
|View full text |Cite
|
Sign up to set email alerts
|

46,XX Male - Testicular Disorder of Sexual Differentiation (DSD): hormonal, molecular and cytogenetic studies

Abstract: SUMMARYThe XX male syndrome -Testicular Disorder of Sexual Differentiation (DSD) is a rare condition characterized by a spectrum of clinical presentations, ranging from ambiguous to normal male genitalia. We report hormonal, molecular and cytogenetic evaluations of a boy presenting with this syndrome. Examination of the genitalia at age of 16 months, showed: penis of 3.5 cm, proximal hypospadia and scrotal testes. Pelvic ultrasound did not demonstrate Mullerian duct structures. Karyotype was 46,XX. Gonadotroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The free softwares Chromas Pro v.1.5 and CLC Sequence Viewer v.6.6.2 were used to analyze and compare sequences with the published WT1 (ENSG00000184937) sequence at Ensembl database (www.ensembl.org). Y-chromosome sequence analysis was conducted by PCR and nested-PCR with primers for SRY gene, TSPY gene and Y-centromeric region DYZ3, as described elsewhere (10). After PCR amplification, reaction products (10 µl) were submitted to 2% agarose gel electrophoresis stained with ethidium bromide and using a molecular weight marker.…”
Section: Methodsmentioning
confidence: 99%
“…The free softwares Chromas Pro v.1.5 and CLC Sequence Viewer v.6.6.2 were used to analyze and compare sequences with the published WT1 (ENSG00000184937) sequence at Ensembl database (www.ensembl.org). Y-chromosome sequence analysis was conducted by PCR and nested-PCR with primers for SRY gene, TSPY gene and Y-centromeric region DYZ3, as described elsewhere (10). After PCR amplification, reaction products (10 µl) were submitted to 2% agarose gel electrophoresis stained with ethidium bromide and using a molecular weight marker.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical phenotypes about 46, XX DSD have been identified to three groups, including males with normal phenotype, males with genital ambiguities and males with true hermaphrodites [3]. Ovotesticular DSD, which is characterized by the presence of both testicular and ovarian tissue in the gonads of the same individual, and testicular DSD characterized by a full development of both gonads as testes without any evidence of ovarian tissue [4]. Approximately 80% of individuals with 46,XX testicular DSD present after puberty with normal pubic hair and normal penile size, but small testes, and sterility resulting from azoospermia [5].…”
Section: Introductionmentioning
confidence: 99%
“…SRY -negative XX males usually have a phenotype similar to Y-positive males but differ in showing genital ambiguity, which is the case in our patient. Alves et al [2010] suggested that negative XX testicular DSD may result due to gain-of-function mutations in one or more genes downstream to the SRY gene pathway or due to a loss of function in some genes associated with the inhibition of male development. It has been postulated that Y-negative XX testicular DSD and XX OT-DSD have a common origin [Toublanc et al, 1993;Kolon et al, 1998], which is supported by many reports of sibship among XX males and XX OT-DSD [Abbas et al, 1990;Ramos et al, 1996;Slaney et al, 1998;Maciel-Guerra et al, 2008].…”
Section: Discussionmentioning
confidence: 99%